The Effect of Chromium and Boron on the Lipid Peroxidation and Antioxidant Status (in Experiment) - IZTLEUOV, Marat; UMIRZAKOVA, Zhanat; IZTLEUOV, Erbolat; SAMBAEVA, Sanimgul; IZTLEUOVA, Gulmira; YESMUKHANOVA, Dariga; AKHMETOVA, Ainur; MEDEUOVA, Raushan; KOLISHBAEVA, Indira (Journal of Environmental Management and Tourism; Vol 8 No 3 (2017): JEMT Volume VIII Issue 3(19) Summer 2017DO - 10.14505//jemt.v8.3(19).04, 2017)
Current anthropogenic factors have a destructive effect on the environment. In this connection, it becomes necessary to study the negative effects of substances on living organisms and ways to reduce them. This article evaluated the impact of potassium dichromate (K2Cr2O7) and boric acid (H3BO3) on the status of lipid peroxidation (LPO) and antioxidant system. The work is performed on 24 male rats of Wistar weighing 180-220 g, were grown in the vivarium of the Central research laboratory of West Kazakhstan state medical University named after Ospanov. An experiment on Wistar rats: 1 st - warning; 2 nd - received K2Cr2O7; 3 rd – H3BO3; 4 th – K2Cr2O7 and H3BO. The introduction of K2Cr2O7 intensified LPO and reduced activity of catalase, glutathione peroxidase and superoxide dismutase, the number of sulfhydryl groups. The results of the study allow asserting that the H3BO3 in the conditions of joint use with K2Cr2O7 has an antioxidant effect, which leads to inhibition of LPO and activation of antioxidant system. Therefore, we first established the antioxidant effect of boric acid in the combined effects of potassium dichromate and boric acid.